Efektivitas Mahasiswa Magang dalam Mendukung Kinerja Bisnis dan Operasional: Studi Kasus pada SEOMUDA.ID dan SPPG Sukabumi Cireunghas - Aldi Bragi; Muhamad Wahyu Hamijaya (North Press, 2026)
This study aims to analyze the effectiveness of internship students in supporting business performance and operational efficiency at two distinct organizations: SEOMUDA.ID, a digital marketing consultancy, and SPPG Sukabumi Cireunghas, a public nutrition service unit. Employing a qualitative case study approach, data were collected through participant observation, task documentation, and weekly reflection notes during five months of internship at SEOMUDA.ID (June–October 2025) and four months at SPPG Sukabumi Cireunghas (October 2025–February 2026). The findings reveal that the intern made significant contributions by producing consistent educational Instagram content that enhanced audience engagement and brand visibility at SEOMUDA.ID, while providing substantial operational support through production supervision, quality control, data management, and stakeholder coordination at SPPG, which improved service efficiency for 3,015 beneficiaries. These results confirm that well-structured internship programs effectively bridge theoretical knowledge with practical application through experiential learning cycles, delivering mutual benefits for students’ competence development and organizational productivity. Practical recommendations for higher education institutions and industry–public service partnerships are provided.